Texture zeros and weak basis transformations - Branco, G. C. (2014)
We investigate the physical meaning of some of the "texture zeros" which appear in most of the Ansatze on quark masses and mixings. It is shown that starting from arbitrary quark mass matrices and making a suitable weak basis transformation one can obtain some of these sets of zeros which therefore have no physical content. We then analyse the physical implications of a four-texture zero Ansatz which is in agreement with all present experimental data. (C) 2000 Elsevier Science B.V. AU rights reserved.